MORPHOMETRIC VARIATION OF ISLAND POPULATIONS OF Macroglossus spp. (Chiroptera : Pteropodidae) - Agustinus Suyanto; Darel K. Kitchener; L. H. Schmitt; Norah K. Copper (BRIN Publishing (Penerbit BRIN), 2004)
A total of 395 skulls and skins of Macroglossus were examined, mostly from Indonesia, and some from Philippines, Papua New Guinea and Australia. The use of discriminant [unction analysis recognized six broad grollps of island populations of Macroglossus: The [aura grollp (Nias, Sumaiera, [auia, Bali and Nusa Penida ls.), the Nusa Tenggara group (Lombok, Sumbawa, Moyo, Komodo, Rinca, Sumba, Flores, Adonara, Lembatu, Paniar, Alor, Timer, Semau, Roti, Sabu, Kalitnanian, Westem Australia, New Britain, New Ireland and Bum), the Suiatuesi group (Sulauiesi onlv), the Siberui group (Siberut only), the New Guinea group (New Guinea only) and the Philippine group (Philippines only). The [aura group is represented by M. sobrinus Andersen, 1911; the other grollps M. minimus (Geoffroy, 1810). Within M. sobrinus, four subspecies were recognized. These were M. s. sobrinus (fawa and Sumaiera); M.s. fratemus (Siberut); M. s. subsp. novo A (Bali and Nusa penida); and M. s. sllbsp. novo B (Nias). Within M. minimus, six subspecies were recognized, these were M. m. minim us (Nusa Tenggara and Western Australia); M. m. nanus (New Britain and New Ireland); M. m. lagochilus (Kalimantan, Buru and Madura); M. m. microtus (New Guinea); M. m. fructivorous (Philippines) and M. m. meyeri (Sulouiesi). The taxa can be separated by discriminant function and unioariate analysis of continuously varying characters, in conjunction with the anterooentral ossification projecting forwards from the den tan symphysis and the fleshy protuberance supported on tile distal end of the lips by this ossification.